ISLAMIC CONTRIBUTION IN THE COVID-19 PANDEMIC VIEWED FROM HISTORY - Muhammad Efendi; Masriyah Masriyah; Selamat Riadi (Abjadia, 2020)
Islam is the religion of rahmatan lil'alamin which regulates all aspects and joints of the life of the Ummah. The pattern of rules that are within the auspices of Islam actually comes from the Qur'an and Hadith. So, it can be said that the studies in the Qur'an and Hadith will always be an interesting study to be discussed in each change of age of the Ummah life, this is because every era will face different problems of life, but there are always similarities in the reasons listed in the study of the Qur'an and The Prophet's hadith. The Covid-19 outbreak that originated in Wuhan China is similar to the plague of leprosy and tha'un during the time of the Prophet Muhammad (PBUH) to His friend, which are both contagious diseases. In this paper the authors use the method of library research as a tool to explore information regarding Islam in dealing with infectious diseases. Basically, Islam has made a major contribution in dealing with all kinds of epidemics including Covid-19 which is happening in this era.